2016
DOI: 10.47657/201617908
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of E-Books among Undergraduate Medical Students at Lahor

Abstract: The purpose of this study is to report on a survey that was carried out to access the perception of the academic users, and their awareness about the use of e-books at existing level. The survey also seeks to find out the preferences of the users regarding the format for using books. A quantitative approach which employs a survey technique was used to collect information on e-books utilization habit among medical students. Statistical analyses were carried out on the data using Software Package for Social Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…These results support the earlier findings by Khan et al . (2016), Rafiq (2014) and Rafiq and Warraich (2016); that the use of e-books was still in the growing stage. Similarly, e-books' use has also been reported to be at a very early stage by Tenopire (2003) and Noorhidawati and Gibb (2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results support the earlier findings by Khan et al . (2016), Rafiq (2014) and Rafiq and Warraich (2016); that the use of e-books was still in the growing stage. Similarly, e-books' use has also been reported to be at a very early stage by Tenopire (2003) and Noorhidawati and Gibb (2008).…”
Section: Discussionmentioning
confidence: 99%
“…In the local context, studies by Rafiq (2014) and Rafiq and Warraich (2016) found greater use of open access e-books as compared to the HEC subscribed e-books among students for academic purposes. In another study, Khan et al (2016) investigated the use of e-books through survey research and reported that the use of e-books among agricultural, engineering and social science students of KPK universities was quite low.…”
Section: Literature Reviewmentioning
confidence: 98%
See 2 more Smart Citations
“…E-books are digital versions of printed books that can be accessed and read through electronic devices such as computers, tablets, smartphones, or electronic reading devices (e-readers). E-Books generally have file formats such as PDF, EPUB, or MOBI that allow readers to read, store, and carry book collections practically in one device [4]- [5]. E-Books have become popular due to their practicality in providing quick access to various reading materials without the need to physically carry a physical book.…”
Section: Introductionmentioning
confidence: 99%